The first successful bone marrow transplantation in Vietnam for a young Vietnamese boy with chronic granulomatous disease: a case report - Nguyen-Thanh, Binh; Nguyen-Ngoc-Quynh, Le; Dang-Thi, Ha; Le-Quynh, Chi; Nguyen-Thi-Van, Anh; Thuc-Thanh, Huyen; Dang-Anh, Duong; Lee, Pamela P.; Cao-Viet, Tung; Tran-Minh, Dien (Frontiers in Immunology, 2023)
Background Chronic granulomatous disease (CGD) is an inborn error of immunity (IEI) disorder that results from defects in the respiratory burst activity in phagocytes, leading to the inability to kill bacterial and fungal microorganisms. CGD patients usually have a high incidence of morbidity such as infections and autoinflammatory diseases and a high mortality rate. Allogeneic bone marrow transplantation (BMT) is the only definitive cure for patients who suffer from CGD. Case presentation We report the first transplant case of chronic granulomatous disease in Vietnam. A 25-month-old boy with X-linked CGD underwent bone marrow transplantation from his 5-year-old, full-matched human leukocyte antigen (HLA)-carrier sibling after myeloablative conditioning regimen with busulfan 5.1 mg/kg/day for 4 days, fludarabine 30 mg/m2/day for 5 days, and rATG (Grafalon-Fresenius) 10 mg/kg/day for 4 days. Neutrophil was engrafted on day 13 posttransplant, donor chimerism was 100% on day 30 with the dihydrorhodamine-1,2,3 (DHR 123) flow cytometric assay test that reached 38% of the normal 45 days posttransplant. Five months after transplant, the patient was free of infection with stable DHR 123 assay at 37%, and donor chimerism remained 100%. No sign of a graft-versus-host disease had been observed posttransplant. Conclusion We suggest that bone marrow transplantation is a safe and effectual cure for CGD patients, especially for patients with HLA-identical siblings.